The impact of instability in latin and South America. - Ellis, R.E.
This article uses a system dynamics methodology to examine the geopolitical significance of narcoterrorism dynamics currently observed in Colombia and the Andean Ridge region. Through influence diagrams, it presents a systemic analysis of the phenomenon. It argues that the interaction between drug production, insurgency is a system characterized by dynamic instability. Moreover, it suggests that the extensive quantity of positive feedback relations in this system could allow the current violence and social chaos could spread across the region and overwhelm the capability of governments to respond, more rapidly than a traditional analysis of narcoterrorism and other regional phenomenon suggests.
Keywords: Andean Ridge region; Latin America; South America; Bioterrorism; Drug production; Dynamic instability; Dynamics methodology; Geopolitical significance; Insurgency; Narcoterrorism; Narcoterrorism dynamics; Positive feedback relations; Social chaos; System dynamics methodology